The Effects of Deradicalization Standardized Policy in Advancing Human Security - Ina Purnaningati Saputro; Sri Endah Wahyuningsih; Josua Natal Andus Muara Tampubolon; Muhammad Zulfan Tanjung; Clarizze Yvoine Mirielle (Contrarius Indonesia, 2026)
Terrorism represents an extraordinary crime because it generates extensive and complex impacts that compel the state to formulate responses beyond purely repressive measures by emphasizing preventive and rehabilitative strategies. The government implements deradicalization programs for terrorist inmates within correctional institutions to reinternalize Pancasila values, transform radical ideologies, and facilitate effective social reintegration. This study analyzes the implementation of deradicalization programs through the perspective of Pancasila values and evaluates the role of correctional institutions within the integrated criminal justice system. This research applies a normative legal method by employing statutory, conceptual, and case approaches and by relying on library-based data derived from legislation, legal doctrines, and relevant academic literature. The findings demonstrate that the legal framework supporting deradicalization programs provides an adequate foundation, yet practical implementation continues to face substantial challenges, including limited institutional capacity, weak internalization of Pancasila values, and the persistence of recidivism among terrorism offenders. These findings indicate that existing policies have not fully achieved their intended objectives. Therefore, this study concludes that the state must strengthen the role of correctional institutions by improving the quality of rehabilitation programs, enhancing coordination among institutions, and developing a more comprehensive approach based on Pancasila values in order to ensure the effectiveness of deradicalization efforts and to advance broader human security objectives.